Konversi Agama Di Desa Lokapaksa Kecamatan Seririt Kabupaten Buleleng (Perspektif Sosial Keberagaman) - I Wayan Gata (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2021)
The process of religious conversion is currently still evident. It is evident that there are some Balinese who have recently converted to Christianity, so this has attracted the attention of researchers to find out the reasons, factors that cause Balinese people in Lokapaksa village to convert to religion. Departing from this phenomenon is very important and interesting to be researched and revealed scientifically without being influenced by certain interests and personal interests, but to reveal the truth about the real process of religious conversion. So far it is not certain what factors caused the problem in Lokapaksa village to convert to another religion. The theories used are phenomenological theory, hegemony theory and structural functionalism theory. The methods are observation, interview, document study, data analysis technique, research result presentation method with descriptive qualitative method, conclusion. Keywords: Religious Conversion, Religious Social Perspective